Potensi Inokulan Petrofilik dan Kompos Kotoran Ayam dalam Bioremediasi Limbah Minyak Bumi Sistem Land Treatment - Pujawati Suryatmana; Richard A. Gunawan; Diyan Herdiyantoro; Mieke Rochimi Setiawati (Soilrens, 2019)
Bioremediation of petroleum waste using the land treatment system is generally carried out by indigenous Petrophilic stimulation as a degrading agent. One of the efforts to improve the performance of the bioremediation system is by adding petrophilic inoculants and organic material as a source of nutrition. This experiment focused on observation of the effect of endogenous petrophilic consortium by adding chicken manure compost towards bioremediation performance parameters, including the efficiency of hydrocarbon degradation, soil pH and petrobacter population on Jatinangor Inceptisols contaminated with petroleum waste. The experiment Design used in this experiment was Factorial Randomized Block Design (FRBD). The first factor was the variation of the concentration  of the petrophilic consortium, consisted of: (i) without a petrophilic consortium, (ii) the concentration of petrophilic consortium 1% (w/ w), (iii) the concentration of petrophilic consortium 3% (w/ w ), (iv) concentration of petrophilic consortium 5% (w/ w). The second factor was the variation of the concentration of chicken manure compost: (ii) without compost chicken manure, (ii) the concentration of chicken manure compost 1.5% (w / w), and (iii) the concentration of chicken manure compost 3% (w/w). ). The results showed that the treatment of exogenous Petrophilic and chicken manure could not significantly improve the biodegradation efficiency of hydrocarbons, but the Petrophilic additives of 3% (w/ w) could increase the highest Petrophilic population. From this study was found that indigenous petrophilic had the potential to degrade hydrocarbons by 71.20%, while the application of exogenous 1% (w/w) petrophilic was able to degrade hydrocarbons by 71.97 %.